How the body shapes the way we think : a new view of intelligence - Pfeifer, Rolf, 1947- (Bradford book., 2007)
An exploration of embodied intelligence and its implications points toward a theory of intelligence in general; with case studies of intelligent systems in ubiquitous computing, business and management, human memory, and robotics.